Methodological Tools to Measure the State of Regional Entrepreneurial Ecosystem - Solodilova, Natalya Zinovyevna; Malikov, Rustam Ilkamovich; Grishin, Konstantin Evgenyevich (Economy of Regions, 2018)
At present, the development of entrepreneurship is a priority task of social and economic development of Russia. We observed rates of socio-economic and innovative development of regions indicate that the private business initiative is not sufficiently developed. At the same time, the private business initiative is the leading driver of economic renewal of the territories. As practice shows, current measures, aimed at stimulating entrepreneurship, do not provide the growth of business activity and seem insufficient. Wiese measures do not consider specific spatial context in which the business develops. Therefore, these reasons significantly reduce the effectiveness of these stimulating measures. In this regard, we estimate that the environment in which the elements of the system interact is gaining a great importance in the framework of a system approach to the study of the entrepreneurship development at the regional level. In practice, to manage the development of business structures in a spatial context, the ecosystem approach seems to be very promising. Wis approach takes into account the nature of the interactions of economic agents and their relationship with the environment. We highlight that the ecosystem approach to entrepreneurship is a transition from a traditional economic view of entrepreneurship, which is market-oriented to a new economic view that emphasizes people, networks and institutions. We substantiate that it is necessary to develop a methodological toolkit for monitoring the attractiveness of a regional entrepreneurial ecosystem for the generation and development of entrepreneurial processes. It is being an important element of the mechanism for designing and managing the development of business ecosystems. To determine the current state of the entrepreneurial ecosystem in a region, we have proposed a methodology for monitoring the state of the regional entrepreneurial ecosystem. Wis method is based on a statistical analysis of the demographic quantitative and qualitative indicators characterizing the intensity of the development and extinction of entrepreneurial processes. As a result, we have expanded the concept of the ecosystem approach. Furthermore, we have justified its application for the investigation of entrepreneurial processes at the regional level. To study the current state of regional entrepreneurial ecosystems, we suggest to use a special statistical apparatus. Wis apparatus is based on demographic indicators characterizing the viability and growth potential of entrepreneurial structures in a specific spatial context. To further develop the ecosystem approach for the study of entrepreneurship at the regional level, there is an urgent need for further research that will allow to identify and understand the patterns of the development of entrepreneurial ecosystems. It will increase the effectiveness of practical measures for designing a mechanism for managing the development of regional entrepreneurship.